Holomech: an extended reality tool for supporting student motivation and perceived spatial reasoning in structural mechanics - Amouzgar, Kaveh; Mousavi, Mahmoud (Virtual reality : the journal of the Virtual Reality Society, 2025)
Spatial intelligence is essential for understanding fundamental and applied engineering concepts, particularly in areas requiring spatial reasoning, such as mechanical engineering. However, traditional teaching methods often struggle to effectively enhance spatial intelligence, making it difficult for students to grasp complex concepts. Extended reality (XR), which includes augmented, mixed, and virtual reality, offers a potential solution by blending real and digital environments to create interactive and engaging learning experiences. This study presents the development and evaluation of HoloMech, an XR-based learning application designed to support the teaching of stress and deformation in beam structures. HoloMech enables students to explore structural mechanics by manipulating loads and observing real-time beam deformation, internal forces, and stresses. The application was developed using Unity, the Mixed Reality Toolkit (MRTK), and custom C# scripts, with cloud-based computation of mechanical responses. The tool was deployed across three engineering programs at under-graduate level. A mixed-method evaluation was conducted using pre- and post-exposure questionnaires to assess students’ perceived motivation, spatial understanding, and cognitive experience. The results indicate that students found HoloMech engaging and helpful for understanding spatially intensive concepts, with reported increases in motivation and reductions in perceived cognitive load. These findings suggest that XR applications like HoloMech can complement traditional instruction and provide valuable pedagogical support in engineering education. Future work will include objective assessments of learning outcomes and cognitive load using validated instruments.